Re-establishment of vegetation on soil contaminated by heavy metals in response to Mexican sunflower and cassava peels composts. (2012)
Soil contamìnation by industriai wastes contributes greatly to poor soil fertility, ecological imbalance and phytotoxicity. To restore soil fertility and encourage plant growth, remediation of contaminated land becomes pertinent. The use of organic amendment has been reported to be effective for restoration of heavy metal contamiflàted soil Effects of Mexican Sunflower (Tithonia diversifolia: MSC) and Cassava peels (Manihot esculentum: CPC) composts, each applied at 20 and 40 t/ha as well as inorganic fertilizer (NPK 20:10:10) applied at 100 kgN/ha were investigated for restoration and re-vegetation of a degraded battery wastes contaminated site. The experiment was laid out in a Randomized Complete Block Design (RCBD). Ordination method was used to measure flora diversity and abundance among treatments. The species ìmportance in thè eco System was determine d using Relative Importance Values (RIV) before application of compost (BAC), at 4 weeks after compost application (4WACA) and at 8 weeks after compost application (8WACA). Also, thè dominance and plant species distribution at thè three periods were determined from thè Dominance, Shannon and Equitabilty indices. Application of composts increased thè number of individuai plants on thè contaminated site from 1177 at BAC to 2276 at 8 WACA. Species richness increased from 7 species at BAC to 15 species at 8 WACA. Gomphrena celosoides L. had thè highest RIV value (72.4%) at BAC, 67.0% and 49.6%> at 4 WACA and 8 WACA respectively. The dominance index (DI) decreased from 0.8557 at BAC to 0.6008 at 8 WACA. At 8 WACA thè Shannon index (0.9976) and Equitability index (0.3684) were highest. Application of MSC at 40t/ha (MSC40) reduced Pb level in thè soil by 71.6% followed by CPC40 (67.3%), MSC20 (66.1%) and least in CPC20 (49.5%). NPK fertilizer application had no effect on soil Pb level compared to control. Addìtion of compost significantly increased thè plant nxutrients including phosphorus, nitrogen, calcium and magnesium in thè soil compared to inorganic fertilizer. The use of compost reduced Pb contamination, improved soil fertility, enhanced re-vegetation and flora diversity of battery waste contaminated site more than inorganic fertilizer. The prevalence of G. celosioides may suggest that it has potentials for thè phytoremediation oflead-acid battery polluted soil.